Tiger reefs: Self‐organized regular patterns in deep‐sea cold‐water coral reefs - van der Kaaden, Anna-Selma; Maier, Sandra R.; Siteur, Koen; De Clippele, Laurence H.; van de Koppel, Johan; Purkis, Sam J.; Rietkerk, Max; Soetaert, Karline; van Oevelen, Dick (Ecosphere, 2023)
Complexity theory predicts that self‐organized, regularly patterned ecosystems store more biomass and are more resilient than spatially uniform systems. Self‐organized ecosystems are well‐known from the terrestrial realm, with “tiger bushes” being the archetypical example and mussel beds and tropical coral reefs the marine examples. We here identify regular spatial patterns in cold‐water coral reefs (nicknamed “tiger reefs”) from video transects and argue that these are likely the result of self‐organization. We used variograms and Lomb–Scargle analysis of seven annotated video transects to analyze spatial patterns in live coral and dead coral (i.e., skeletal remains) cover at the Logachev coral mound province (NE Atlantic Ocean) and found regular spatial patterns with length scales between 62 and 523 m in live and dead coral distribution along these transects that point to self‐organization of cold‐water coral reefs. Self‐organization theory shows that self‐organized ecosystems can withstand large environmental changes by adjusting their spatial configuration. We found indications that cold‐water corals can similarly adjust their spatial configuration, possibly providing resilience in the face of climate change. Dead coral framework remains in the environment for extended periods of time, providing a template for spatial patterns that facilitates live coral recovery. The notion of regular spatial patterns in cold‐water coral reefs is interesting for cold‐water coral restoration, as transplantation will be more successful when it follows the patterns that are naturally present. This finding also underlines that anthropogenic effects such as ocean acidification and bottom trawling that destroy the dead coral template undermine cold‐water coral resilience. Differences in the pattern periodicities of live and dead coral cover further present an interesting new angle to investigate past and present environmental conditions in cold‐water coral reefs.